Model Adaptasi Bencana Banjir di Kabupaten Kampar Provinsi Riau - Nadiya Sari; Dedi Hermon (Postgraduate, University of Mataram, 2025)
Flood disaster risk reduction in Indonesia still focuses on structural measures with limited research examining community adaptation models. Adaptation models play an important role in planning future disaster mitigation actions. This study aims to determine the response and adaptation model in managing flood disasters by the people of Kampar Regency. Data collection was done by interviews, questionnaires on physical adaptation and social adaptation and questionnaires then FGD (Focus Group Discussion) and analyzed with AHP (Analytical Hierarchy Process). The results show that the level of flood vulnerability from the analysis of the flood vulnerability map in Kampar Regency shows that most of its areas are in the flood-prone category, Land characteristics at four sample points in Kampar Regency show significant variations. As seen in the flood vulnerability map, there are land characteristics of high hazard zones, land characteristics of medium flood hazard zones, land characteristics of low flood hazard zones and flood-free flood hazard zones, and formulating an Adaptation Model using the AHP approach through Focus Group Discussion (FGD). The results of the analysis show a pairwise priority value for land characteristics (0.03), and the level of flood vulnerability (0.03). The weight of the criteria shows land characteristics (0.105) and the level of flood vulnerability (0.258). Indicates the highest alternative is to assess the ability of the soil to absorb water. This alternative can reduce the risk of flood disaster in the study area. These findings indicate the need for special attention to flood-prone areas in Kampar Regency, Riau Province.